Great Expectations as a Pre-Postmodern Rewriting of The Odyssey? - Alain Jumeau (Cahiers Victoriens et Edouardiens)
The postmodern age in literature is characterized by, among other things, a tendency to rewrite classic masterpieces. And there have been, indeed, modern rewritings of Dickens’s novels. Great Expectations is a case in point. Yet this literary game did not really start in the postmodern age and I would like to argue here that Great Expectations—written many decades before Joyce’s Ulysses—might be read as a rewriting of The Odyssey. The comparison between Victorian novel and classic epic is suggested by Dickens’s text itself, in a remarkable piece of rhetoric published by Pumblechook in the local paper. If we take The Odyssey as paradigm, of course we notice many differences in Great Expectations, but also striking similarities. This may be an invitation to read Great Expectations not only as a spiritual odyssey for the Victorian Age, but as a pre-postmodern rewriting of one of the oldest literary masterpieces.